Methodological, reporting, and evidence quality of systematic reviews of traditional Chinese medicine for ischemic stroke - Sun, Shouyuan; Zhao, Liang; Zhou, Xiaoli; Liu, Xuewu; Xie, Zongzhi; Ren, Jun; Zhou, Baoyuan; Pan, Yawen (Frontiers in Pharmacology, 2023)
Objective: The aim of this study is to critically appraise whether published systematic reviews/meta-analyses of traditional Chinese medicine for adults with ischemic stroke are of sufficient quality and to rate the quality of evidence using the Grading of Recommendations, Assessment, Development, and Evaluation approach. Method: A literature search was performed in the Cochrane Library, PubMed, Chinese National Knowledge Infrastructure, and SinoMed databases by March 2022. The inclusion criteria were systematic reviews/meta-analyses of traditional Chinese medicine in adults who suffered from ischemic stroke. A Measurement Tool to Access Systematic Reviews 2 (AMSTAR-2) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Abstract (PRISMA-A) statements were used to assess the methodological and reporting quality of the included reviews. The Grading of Recommendations, Assessment, Development, and Evaluation system was utilized to assess each report’s evidence level. Results: Of the 1,908 titles and abstracts, 83 reviews met the inclusion criteria. These studies were published between 2005 and 2022. The results of AMSTAR-2 showed that 51.4% of the items were reported, but the registration, reasons for the inclusion of study design, the list of excluded studies, and funding information were ignored in the majority of the reviews. The results of PRISMA-A showed that 33.9% of items were reported, and the information on registration, limitation, and funding was not available in many publications. The assessment of the evidence with the Grading of Recommendations, Assessment, Development, and Evaluation showed that more than half (52/83) of the included studies had either low or very low levels of evidence. Conclusion: The reporting quality in the abstract of systematic reviews/meta-analyses on traditional Chinese medicine for ischemic stroke is poor and does not facilitate timely access to valid information for clinical practitioners. Although the methodological quality is of a medium level, this evidence lacks certainty, especially with a high risk of bias in individual studies.